Synopsis: Constraints for small-scale private irrigation systems in the North Central zone of Nigeria - Takeshima, Hiroyuki; Edeh, Hyacinth O. (International Food Policy Research Institute, 2017)
Using nationally-representative farm household data and a case study in the North Central zone, this study shows that, first, the share of small-scale farmers in Nigeria who intensively irrigate some of their crops has declined in recent years, while the share of irrigating farmers who engage in less intensive irrigation has increased. Secondly, high production costs, particularly labor costs, are the major constraints to intensive irrigation.